2003
DOI: 10.1103/physrevb.68.014415
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic release of the residual zero-point entropy in the spin ice compoundDy2Ti2O

Abstract: We report the specific heat and entropy of single crystals of the spin ice compound Dy 2 Ti 2 O 7 at temperatures down to 0.35 K. We apply magnetic fields along the four characteristic directions ͓100͔, ͓110͔, ͓111͔, and ͓112͔. Because of Ising anisotropy, we observe anisotropic release of the residual zero-point entropy, attributable to the difference in frustration dimensionality. In the high magnetic field along these four directions, the residual entropy is almost fully released and the activation entropy … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
77
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(84 citation statements)
references
References 22 publications
4
77
3
Order By: Relevance
“…The kagome lattice is a two-dimensional structure composed of corner-sharing triangles. It is an essential component of the pyrochlore spin ice structure [10,[18][19][20] and has also been connected with jarosite frustrated magnets [17,21]. Compared to the 2-in-2-out ice rule for the pyrochlore structure, the ice rule here changes to 2-in-1-out or 1-in-2-out for each vertex (see Our realization of the kagome structure is fabricated from permalloy (Ni 80 Fe 20 ) using conventional electron-beam lithography, followed by metal deposition and lift-off.…”
Section: Textmentioning
confidence: 99%
“…The kagome lattice is a two-dimensional structure composed of corner-sharing triangles. It is an essential component of the pyrochlore spin ice structure [10,[18][19][20] and has also been connected with jarosite frustrated magnets [17,21]. Compared to the 2-in-2-out ice rule for the pyrochlore structure, the ice rule here changes to 2-in-1-out or 1-in-2-out for each vertex (see Our realization of the kagome structure is fabricated from permalloy (Ni 80 Fe 20 ) using conventional electron-beam lithography, followed by metal deposition and lift-off.…”
Section: Textmentioning
confidence: 99%
“…One obvious field orientation that satisfies this condition is the [112] direction, first investigated in Ref. [19]. Measurements on a single crystal of Dy 2 Ti 2 O 7 with H aligned along the [112] direction revealed two broad specific heat peaks and no sign of a phase transition [19].…”
mentioning
confidence: 99%
“…For the [111] direction, the frustration structure changes from that of a three-dimensional pyrochlore to that of a twodimensional Kagome-like lattice with constraint, leading to different values of the zeropoint entropy. [5] The combination of ferromagnetic coupling and Ising anisotropy may be a reason for the strong frustration. But how the spins interact with each other is not well understood in the spin ice materials.…”
Section: Introductionmentioning
confidence: 99%
“…"Spin ice" materials governed by the same statistical mechanics of so-called "ice rule" as the hydrogen atoms in the ground state of ordinary hexagonal ice I h have macroscopically degenerate ground states down to almost zero temperature. [1,2,3,4,5,6,7,8,9] Experimentally, the observed value of (1/2)Rln(3/2) through specific heat measurement [1] is consistent with what is expected by pauling's theory, while the spin entropy only freezes out below about 4 K. [2] From magnetic susceptibility studies, a strongly frequency dependent cooperative spin freezing is observed at about 16 K, which is associated with a very narrow distribution of spin relaxation times and a sharp drop at about 2 K. [3,6] Neutron scattering studies performed by Fennell et al [4] also well demonstrate the spin ice state and the coexistence of long range ferromagnetic and short range antiferromagnetic order in a magnetic field applied along the [110] axis of Dy 2 Ti 2 O 7 . In theoretical aspect, R.G.…”
Section: Introductionmentioning
confidence: 99%